(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This article explores the phenomenon of speech counteraction in English dialogue within the context of literary works from the 20th and 21st centuries. By examining the methods employed by authors to depict and resolve conflicts through dialogue, we aim to gain insight into the evolving dynamics of communication in literature over the years.